Spontaneous myomectomy after GnRH agonist treatment: Case report - Atilgan, Remzi; Simsek, Mehmet; Özkan, Zehra Sema; Pinar, Gülser Göktolga; Atli, Hasine Gölge; Orak, Ugur; Sapmaz, Ekrem (My University, 2013)
Uterine fibroids are benign tumors which grow out of uterine smooth muscle and se en in at least %20 of women older than 35 years. They cause bleeding, sense of pressure and recur rent pregnancy losses. Submucous myomas also cause necrosis and infections. Histeroscopic resection may be offered for large submucous and intramural fibroids after GnRH agonist treat ment in order to minimize fibroid size, decrease bleeding amount during the operation and treat anemia before the operation. Here we present a case of spontaneous myomectomy after 3 months of GnRH agonist treatment before histeroscopic resection in a 37 year old woman with submuco us fibroid. GnRH agonist treatment for submucous fibroids, decreases fibroids size, simplifies his teroscopic resection and may result in spontaneous myomectomy as presented in our case. Hence we suggest administration of GnRH therapy for large submucous myomas. Copyright © 2013 by Türkiye Klinikleri.
GnRH agonist tedavisi sonrasi spontan miyomektomi1
Keywords: Goserelin; Hysteroscopy; Leiomyoma